Case Study: Reclassifying a Children's and Young Adult Literature Collection. Issue 2 (3rd April 2022) - Webster, Elizabeth; Faulkner, Autumn
Abstract: The Children's and Young Adult Literature Collection at Michigan State University is more than five years old and was born out of a need to support the teacher education curriculum. The collection focuses on award-winning books as well as those with a diverse aspect either in author, character, and/or subject. The collection was started in collaboration with faculty in the College of Education's teacher education department and initially funded through a diversity grant. At the time the collection was built, it was decided that it would be classified in LCC call numbers as it is housed within a main academic library as a specialty sub-collection (rather than in a curriculum materials center or a dedicated education library). This collection is among the most widely circulated in the library and is robustly used by students in the program. The focus for these past few years has been on building the collection and maintaining the relationships that the collection supports. Over time, the collection has grown substantially and more space was allotted to accommodate it. Using LC classification made sense initially but as the collection expanded, it became somewhat unwieldy. After observing students using the collection, it was apparent that a reorganization of the collection would remove numerous pain points including obstacles to discovery. The timing was serendipitous; a new education librarian with teaching experience and expertise in children's literature had just started and was eager to undertake such a project. This case study will explain all the steps of undertaking this project and include both public services and technical services perspective. Both are essential in considering such an undertaking. Early discussions of the project resulted in a decision to reclass titles from LCC to Dewey, and to abandon the somewhat arbitrary division of picture books and chapter books in favor of an array of shelving categories: fiction, nonfiction, poetry, and graphic novels, with age range designations of children's, middle grade, and young adult. These decisions involved cataloger re-training, changes to labeling and shelving procedures, and space considerations. The authors will explain the rationales behind these decisions and methods used to implement them.